2004
DOI: 10.1002/nau.20038
|View full text |Cite
|
Sign up to set email alerts
|

The risk of hyponatremia in older adults using desmopressin for nocturia: A systematic review and meta‐analysis

Abstract: Hyponatremia is a relatively common adverse effect of the use of desmopressin for the treatment of nocturia and caution and regular monitoring should be part of the use of this management option for nocturia in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 35 publications
2
33
0
8
Order By: Relevance
“…Among the patients with serum sodium levels below normal range 2/3 never dropped below 130 mmol/L. The prevalence of hyponatremia found is similar to that described in a recent meta-analysis (Weatherall, 2004), which among other trials included the all male study in the present analysis. A previous trial in elderly indicated that the risk of desmopressin-induced hyponatremia increased with age, cardiac disease and increasing 24-hour urine volume (Rembratt et al, 2003).…”
Section: Resultssupporting
confidence: 84%
“…Among the patients with serum sodium levels below normal range 2/3 never dropped below 130 mmol/L. The prevalence of hyponatremia found is similar to that described in a recent meta-analysis (Weatherall, 2004), which among other trials included the all male study in the present analysis. A previous trial in elderly indicated that the risk of desmopressin-induced hyponatremia increased with age, cardiac disease and increasing 24-hour urine volume (Rembratt et al, 2003).…”
Section: Resultssupporting
confidence: 84%
“…A gyógyszer hatására a nátrium változatlan szekréciója mellett víz retineálódik, amely során relatív dilúciós hyponatrae mia jön létre, és a szérum ozmolaritás csökken. Incidenciája 7,4% körülire tehető (15). Hyponatraeima kialakulásának veszélye egyidejűleg szedett triciklikus antidepresszánsok, szerotonin visszavételgátlók, chlorpromazin, carbamazepin, loperamid, NSAID-ok esetén fokozódik.…”
Section: Gyógyszeres Kezelésunclassified
“…Dezmopresszin terápiás alkalmazásakor elengedhetetlen a szé-rumnátriumszint rendszeres monitorizálása a súlyos szövődmények elkerülése céljából [37,38]. Mint már ír-tuk, a dezmopresszin nők esetében jobb hatásfokú, így alacsonyabb terápiás dózis beállítása szükséges.…”
Section: Kezelésunclassified
“…Egy 7 tanulmányt feldolgozó metaanalízis alapján a dezmopresszinterápiához kapcsolódó következményes hyponatraemia átlagos előfordulása 7,6% volt (95% CI 3,7-15,1) [38].…”
Section: Kezelésunclassified